Analysis of the effects of expenditure for employees as an essential component of public expenditure on the reduction of regional inequalities in the Western Balkan countries - Janković Gordan; Golubović Miloš (Trendovi u Poslovanju)
Public expenditure represents the cost that each state has to finance state functions and social needs. A significant place in public expenditures is occupied by expenditures for employees, which are included in current budget expenditures. Expenditures for employees in the state budget include all expenses related to salaries and benefits paid to employees in state institutions. The main function of these expenditures is to finance the salaries of employees in the public sector and create social peace. However, by performing this function, expenditures for employees also have the role of reducing inequality among different activities, economic areas, branches, and even among regions. For this reason, this paper examines the influence on the reduction of regional inequalities in Serbia and neighboring countries. It is important to note that expenditures for employees in the state budget differ from state to state and can vary significantly depending on employment policies, salary standards, and other factors. Also, these expenditures may be subject to changes in accordance with budgetary constraints and the economic situation of the state. Southeastern European countries can achieve quality results in the process of improving business processes, but they need a common platform through which the domino effect of successful economic reforms would be realized.